SILENT MYOCARDIAL ISCHEMIA AMONG ASYMPTOMATIC TYPE-2 DIABETIC PATIENTS - Atif Ihsan; Sher Bahadur Khan (Journal of Postgraduate Medical Institute, 2022)
Objective: To determine the frequency of silent myocardial ischemia among asymptomatic type-2 diabetes mellitus patients. Methodology: This was a Cross sectional descriptive study conducted, after approval from the institutional ethical and research committee. A total of 90 asymptomatic type-2 diabetic patients were recruited for the present study. After informed written consent participants were subjected to a symptom-limited exercise tolerance test to detect the presence of silent myocardial ischemia. Descriptive statistics were applied to find frequencies and percentages for qualitative variables, and mean and standard deviation was used for quantitative variables. SPSS version22 was used for data analysis. Results: Among 90 type-2 asymptomatic diabetic patients, the frequency of silent myocardial ischemia was 36.7% (n=33). The frequency of silent myocardial ischemia among males and females was 57.6% and 42.4% respectively. Frequency of silent myocardial ischemia was found significantly more among patients with family history of CAD (60.6% vs 39.4%; p=0.029), prolonged duration of diabetes (15.2% vs 22.2% vs 63.6%; p=0.026) and group of patients with older age (9% vs 39.4 vs 51.6%; p=0.034). With respect to hypertension, smoking, obesity, and gender didn’t show statistically significant variation in the occurrence of silent myocardial ischemia. Conclusion: More than one third patients of asymptomatic type-2 diabetes mellitus had silent myocardial ischemia. Those with a family history of CAD, prolonged duration of diabetes, and participants with older age were more at risk of underlying silent myocardial ischemia.